Polyarginine Interacts More Strongly and Cooperatively than Polylysine with Phospholipid Bilayers - Robison, Aaron D; Sun, Simou; Poyton, Matthew F; Johnson, Gregory A; Pellois, Jean-Philippe; Jungwirth, Pavel; Vazdar, Mario; Cremer, Paul S (The journal of physical chemistry. B, 2016)
The interactions of two highly positively charged short peptide sequences with negatively charged lipid bilayers were explored by fluorescence binding assays and all-atom molecular dynamics simulations. The bilayers consisted of mixtures of phosphatidylglycerol (PG) and phosphatidylcholine (PC) lipids as well as a fluorescence probe that was sensitive to the interfacial potential. The first peptide contained nine arginine repeats (Arg9), and the second one had nine lysine repeats (Lys9). The experimentally determined apparent dissociation constants and Hill cooperativity coefficients demonstrated that the Arg9 peptides exhibited weakly anticooperative binding behavior at the bilayer interface at lower PG concentrations, but this anticooperative effect vanished once the bilayers contained at least 20 mol % PG. By contrast, Lys9 peptides showed strongly anticooperative binding behavior at all PG concentrations, and the dissociation constants with Lys9 were approximately 2 orders of magnitude higher than with Arg9. Moreover, only arginine-rich peptides could bind to the phospholipid bilayers containing just PC lipids. These results along with the corresponding molecular dynamics simulations suggested two important distinctions between the behavior of Arg9 and Lys9 that led to these striking differences in binding and cooperativity. First, the interactions of the guanidinium moieties on the Arg side chains with the phospholipid head groups were stronger than for the amino group. This helped facilitate stronger Arg9 binding at all PG concentrations that were tested. However, at PG concentrations of 20 mol % or greater, the Arg9 peptides came into sufficiently close proximity with each other so that favorable like-charge pairing between the guanidinium moieties could just offset the long-range electrostatic repulsions. This led to Arg9 aggregation at the bilayer surface. By contrast, Lys9 molecules experienced electrostatic repulsion from each other at all PG concentrations. These insights may help explain the propensity for cell penetrating peptides containing arginine to more effectively cross cell membranes in comparison with lysine-rich peptides.
Keywords: polylysin; Lipid Bilayers; peptidy; fosfolipidy; Polylysine; lipidové dvojvrstvy; Phospholipids; Peptides